Effect of Rheum ribes L. juice on the survival of Listeria monocytogenes, Escherichia coli O157:H7 and Salmonella Typhimurium and chemical quality on vacuum packaged raw beef - Incili, Gokhan Kursad; Aydemir, Mehmet Emin; Akgol, Muzeyyen; Kaya, Busra; Kanmaz, Hilal; Oksuztepe, Gulsum; Hayaloglu, Ali Adnan (Elsevier, 2021)
The aim of this study was to evaluate Rheum ribes L. juice as a marinade against L. monocytogenes, E. coli O157:H7 and S. Typhimurium in vacuum packed raw beef. The juice was used at levels of 10%, 50%, and 100% for different marination times (2, 6 or 24 h). E. coli O157:H7 and S. Typhimurium counts in the marinated samples at 100% conc. for 24 h were found as 1.1 and 1.7 log(10) lower than the control group on day 0, respectively (P < 0.05). L. monocytogenes count was found approx. 3.0 log(10) lower than the control group on day 15 (P < 0.05). Total viable count, psychrotrophic bacteria, LAB counts, and pH values were found lower in the 100% conc. marinated samples than control group on day 0 (P < 0.05). A total of 22 volatiles were identified in Rehum ribes L. juice, and ethanol, ethylbenzene and xylene were found as major compounds. Observations showed that the juice exhibited strong antimicrobial activity against tested pathogens depending on the concentrations and marination time. In conclusion, it can be derived that Rheum Ribes L. juice can be used as an acidulant for the decontamination of meat and meat products, and can be a major component of marinades.
Keywords: Rheum ribes L.; Raw beef; E. coli O157:H7; Listeria monocytogenes; Salmonella typhimurium